Specification and Verification of Object-Oriented Software - Leino, Rustan (Marktoberdorf International Summer School 2008, 2008)
The specification of object-oriented and other pointer-based programs must be able to describe the structure of the program’s dynamically allocated data as well as some abstract view of what the code implements. The verification of such programs can be done by generating logical verification conditions from the program and its specifications and then analyzing the verification conditions by a mechanical theorem prover. In these lecture notes, I present an object-based language, Dafny, whose specifications use the style of dynamic frames. I show how to write and specify programs in Dafny. Most of the material is devoted to how to build a first-order automatic program verifier for Dafny programs, generating the verification conditions as input to an automatic satisfiability-modulo-theories solver.